The Legacy of Andries Nentjes - Edwin Woerdman; Yoram Krozer; Johannes Platje (The Central European Review of Economics and Management (CEREM), 2020)
Aim: The aim of this paper is to provide a brief overview of the life and work of Professor Andries Nentjes, who passed away early 2019. As one of the founding fathers of environmental economics in the Netherlands, he contributed in particular to the international literature on market-based pollution control. We wish to honour the legacy of Andries Nentjes by outlining some highlights of his impressive academic research and by showcasing his active contributions to a more sustainable society.
Keywords: 330